2020
DOI: 10.3390/cancers12040794
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Combined Hepatocellular and Cholangiocarcinoma

Abstract: Combined hepatocellular and cholangiocarcinoma (HCC-CC) is a rare primary liver cancer. It is constituted by neoplastic cells of both hepatocellular and cholangiocellular derivation. Different histology types of HCC-CC have been reported, hinting at heterogeneous carcinogenic pathways leading to the development of this cancer. Due to its rarity and complexity, mixed HCC-CC is a scantly investigated condition with unmet needs and unsatisfactory outcomes. Surgery remains the preferred treatment in resectable pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 75 publications
0
33
0
Order By: Relevance
“…Lymph node infiltration was associated with poor survival of cHCC-CC after surgery 15 , 24 . In the present study, the incidence of lymph node infiltration in cHCC-CC was 13.3% and patients with positive LN infiltration survived significant poor prognosis than those negative (median overall survival time, positive vs. negative, 22.1 months vs. 12.9 months, p= 0.019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lymph node infiltration was associated with poor survival of cHCC-CC after surgery 15 , 24 . In the present study, the incidence of lymph node infiltration in cHCC-CC was 13.3% and patients with positive LN infiltration survived significant poor prognosis than those negative (median overall survival time, positive vs. negative, 22.1 months vs. 12.9 months, p= 0.019).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, Kim et al reported that TACE could significantly improve the OS of unresectable cHCC-CC, with a favorable median OS time of 12.3 months 31 . As we know, tumor hypovascularity was the major factor restricting the response of TACE 24 , 31 . Although some studies insisted that cHCC-CC was hypovascular and TACE was not recommended 32 , 33 , the rate of hypervascularity in cHCC-CC in previous study reached about 40.9%-80% 31 , 34 , which enabled a favorable feasibility and effect of applying postoperative TACE for cHCC-CC.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic properties of CHCC-CCA differ from those of HCC and ICC. Moreover, its OS rate has been reported to be even lower than that of ICC (26)(27)(28). As a result, it is critical to separately map prediction models for strong prognostic parameters, including MVI, satellite nodules and LNM.…”
Section: Prognostic Value Of the Predicted MVI Risk Status And Satellite Nodule Statusmentioning
confidence: 99%
“…Locoregional treatments have been considered in CHC that is surgically unresectable with no clear guidelines. Inoperability is usually defined as large or multifocal tumors [58]. CHC follows a pathological course as with HCC.…”
Section: Combined Hepatocellular Cholangiocarcinomamentioning
confidence: 99%